1978
DOI: 10.1111/j.1399-0004.1978.tb02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid disorder in Down syndrome

Abstract: Thyroid function has been studied in 121 patients between 13 and 48 years old with proven Down syndrome. Chemically, hypothyroidism was found in 17 % and hyperthyroidism in 2.5 % of the patients; 18 % of patients had goiter. Thyroid antibodies were detected in 33 % of subjects studied. The abnormal findings were almost equally distributed between the sexes above 20 years of age; however, females had significantly more thyroid disease than males in the younger age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Other studies have shown a female predominance of 3:1 between infancy and adolescence,11 12 although not as high as the 4.2:1 ratio described by de Vries et al in children and adolescents with Hashimoto's thyroiditis 13. As expected in this screened population, there was a low prevalence of hypothyroid symptoms, which were reported in only one third of patients.…”
Section: Discussionsupporting
confidence: 56%
“…Other studies have shown a female predominance of 3:1 between infancy and adolescence,11 12 although not as high as the 4.2:1 ratio described by de Vries et al in children and adolescents with Hashimoto's thyroiditis 13. As expected in this screened population, there was a low prevalence of hypothyroid symptoms, which were reported in only one third of patients.…”
Section: Discussionsupporting
confidence: 56%
“…Our finding of hypothyroidism (15%) in patients with Down's syndrome is comparable with the prevalence rates of The age distribution of hypothyroidism cases is shown in Table-III. [15][16][17][18][19] The variation in prevalence in these earlier studies might be related to the age variation among the studied subjects and/or to differences in diagnostic criteria.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the large series studying thyroid function in Down's syndrome report that hypothyroidism is more common (17 to 40%) while only 0.6-2.5% of patients have hyperthyroidism [4][5][6][7][8] . It rarely presents before eight years of age.…”
Section: Discussionmentioning
confidence: 99%